Patient, Disease, and Drug-Related Risk Factors Associated with Phenytoin- Induced Cutaneous Adverse Drug Reactions in South Indian Epileptic Patients - A Prospective Case-Control Study - John, Shobana; Canyuk, Bhutorn; Anand, T.C. V.; Sukasem, Chonlaphat; Pattharachayakul, Sutthiporn (Current Drug Safety, 2022)
Background: Phenytoin is the most commonly reported aromatic Anti-Epileptic Drug (AED) to cause Cutaneous Adverse Drug Reactions (CADRs). Cutaneous adverse drug reactions may be immune or non-immune mediated. It has been observed that predisposition is multifactorial and that gene mutations alone cannot be the cause. Objectives: In this study, we investigated the patient, disease, and drug-related risk factors associated with phenytoin-induced cutaneous adverse drug reactions in South Indian epileptic patients. Methods: This study was conducted as a single-center prospective case-control study over a period of 13 months. The Fisher’s exact test and multivariate binary logistic regression analysis were used to test the association of single and multiple variables, respectively. Results: This study comprised 26 patients with phenytoin-induced cutaneous adverse drug reactions (PHT-CARDs) and 32 phenytoin-tolerant controls with a mean age of 40.60±18.15 and 36.21±14.71 years, respectively. Among 26 phenytoin-induced cutaneous adverse drug reactions, 76.92% cases were mild-moderate reactions and 23.07% were severe. The onset latency period of these reactions ranged from 7-42 days. The multivariate analysis showed that multiple AEDs (OR =18.62, 95% CI 4.28-80.87, p=< .001) and comorbidities (OR= 5.98, 95% CI 1.33-26.78, p=.01) are risk factors for PHT-CADRs. PHT-SCARs were shown to be associated with previous allergy history (OR= 31, % CI 2.40-398.8, p=.008). Conclusion: The risk factors found to be associated with CARDs in South Indian Epileptic patients are multiple AEDs, comorbidities, and past allergic history. Therefore, physicians and other associated health care professionals should closely monitor the patients when phenytoin is employed.
Keywords: Cutaneous Adverse Drug Reactions (CADRs)